Tanatologičeskie motivy «Strašnoj mesti» Nikolaja Gogolja v kontekste ètnokul’turnyh svjazej ukraincev The Thanatological Motifs of A Terrible Vengeance Story by Mykola Gogol in the Context of the Ethnocultural Connections of the Ukrainians - Rakhno, Kostyantyn (Studia mythologica Slavica, 2019)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This article deals with the description of the posthumous destiny of the dead in the horror story A Terrible Vengeance by Mykola Gogol. It describes the patrimonial cemetery of the sorcerer, where all his ancestors were buried. Their corpses rise from their graves, but the first local dead man, the largest of them, cannot rise, and his movements cause earthquakes. These images can be fully understood only in comparison with Chuvash beliefs about the first buried dead person as the cemetery master and also with Zoroastrian and Ossetian mythological concepts. The Chuvashes and the Iranian-speaking nations, primarily the Ossetians, have parallels to the plot about a father coveting his daughter and killing his grandchild, the soul’s wanderings during sleep, and other related motifs. Thus, the folkloric motifs on which the story is constructed help to reveal the ethnocultural connections of the early Ukrainians.